Magnetic increases with central current sheets: Observations with Parker Solar Probe - Fargette,N; Lavraud,B; Rouillard,A; Eastwood,JP; Bale,SD; Phan,T; Øieroset,M; Halekas,JS; Kasper,J; Berthomier,M; Case,AW; Korreck,KE; et al. (Astronomy & Astrophysics, 2021)
Aims. We report the observation by Parker Solar Probe (PSP) of magnetic structures in the solar wind that present a strong peak intheir magnetic field magnitude with an embedded central current sheet. Similar structures have been observed, either at the Earth’smagnetopause and called interlinked flux tubes, or in the solar wind and called interplanetary field enhancements.Methods. In this work, we first investigate two striking events in detail; one occurred in the regular slow solar wind on November 2,2018 and the other was observed during a heliospheric current sheet crossing on November 13, 2018. They both show the presenceof a central current sheet with a visible ion jet and general characteristics consistent with the occurrence of magnetic reconnection.We then performed a survey of PSP data from encounters 1 to 4 and find 18 additional events presenting an increase in the magneticfield magnitude of over 30% and a central current sheet. We performed a statistical study on the 20 "magnetic increases with centralcurrent sheet" (MICCS), with 13 observed in the regular slow solar wind with a constant polarity (i.e., identical strahl direction), and7 which were specifically observed near a heliospheric current sheet (HCS) crossing.Results. We analyze and discuss the general properties of the structures, including the duration, location, amplitude, and magnetictopology, as well as the characteristics of their central current sheet. We find that the latter has a preferential orientation in the TNplane of the RTN frame. We also find no significant change in the dust impact rate in the vicinity of the MICCS under study, leadingus to conclude that dust probably plays no role in the MICCS formation and evolution. Our findings are overall consistent with adouble flux tube-configuration that would result from initially distinct flux tubes which interact during solar wind propagation.